Hypertrophic Osteoarthropathy: A Secondary Manifestation of Malignant Melanoma - Malaty, Shiva; Gupta, Aditya (Case Reports in Rheumatology, 2021)
Background. Hypertrophic osteoarthropathy (HOA) is a rare finding in the setting of metastatic melanoma. A majority of cases of secondary HOA involve lung malignancies. Evaluation of presenting symptoms such as polyarthralgia and clubbing followed by review of imaging studies are diagnostic steps for HOA. Case Presentation. We present a 60-year-old female with a history of metastatic melanoma who presented with bilateral and symmetric polyarthralgia and clubbing. A plain film radiograph demonstrated periosteal thickening involving the metacarpals and proximal phalanges as well as the distal radius and ulna, consistent with HOA. The patient was treated with nonsteroidal anti-inflammatory agents for supported care. Conclusion. HOA may be a secondary manifestation of metastatic melanoma. Recognition and supportive care of this condition may lead to improved quality of life for patients.